Origin and implications of orbital-induced sedimentary cyclicity in Pliocene well-logs of the Western Mediterranean - Ochoa D. (2018)
The climatic origin of astronomically induced sedimentary cycles in the Mediterranean and adjacent areas during the late Neogene and Quaternary remains puzzling; as cycles have been linked to concomitant but seasonally opposite changes in African summer monsoon precipitation (Eastern Mediterranean sapropels) and Atlantic regulated winter-precipitation (carbonate cycles on the Atlantic side of the Mediterranean). Particularly, little is known about the cyclic sedimentation on orbital time scales in the Western Mediterranean, with the prime exception of the Messinian sapropels from the Sorbas basin (southern Spain). Here we show that regular alternations in Pliocene downhole logs from the industrial drill-site Muchamiel-1, located along the Balearic Promontory in the Western Mediterranean, are related to eccentricity (bundles) and to obliquity and precession cycles (basic meter-scale alternations). We establish an astronomically based age model for the interval between 5.33 and 2.8 Ma, by first correlating cycle bundles to eccentricity and then the basic dominantly precession-related cycles to the 65°N summer insolation of La2004. The striking bed-to-bed similarities between the Muchamiel-1 well-logs and other records from both the Atlantic margin and the Central Mediterranean suggest that the same climatic forcing was responsible for the formation of carbonate cycles across the Western Mediterranean and adjacent Atlantic. We conclude that formation of alternating carbonate-rich/carbonate-poor beds was controlled by Western Mediterranean cyclogenetic mechanisms as well as by peri-Mediterranean precipitation associated with changes in the North Atlantic System (NAS). These findings highlight the importance of peri-Mediterranean precipitation on the sedimentary cyclicity by dictating terrigenous (clay) supply and potentially on the hydrology of the basin by providing additional freshwater required for sapropel formation. Consequently, cyclic sedimentation in the Mediterranean results from the combined effect of precipitation changes driven by (i) the North African monsoon, (ii) the Atlantic system, and (iii) intrabasinal Mediterranean atmospheric dynamics. © 2018 Elsevier B.V.